Antibacterial mechanism of linalool against L. monocytogenes, a metabolomic study. (February 2022) - He, Rongrong; Chen, Weijun; Chen, Haiming; Zhong, Qiuping; Zhang, Hailing; Zhang, Ming; Chen, Wenxue
Abstract: Listeria monocytogenes ( L. monocytogenes ) is a highly pathogenic microorganism that can cause food contamination and a series of foodborne diseases. Linalool is widely used in the food processing industry due to its excellent antibacterial properties. But its antimicrobial mechanism against L. monocytogenes has scarcely been reported based on metabolomics technology. In this study, the activity of linalool against L. monocytogenes and its effect on cell membrane damage were investigated. Meanwhile, the activity of key enzymes in respiratory metabolism was determined. Moreover, untargeted metabolomics was applied to evaluate the inhibiting mechanism on L. monocytogenes . Our results indicated that linalool showed a strong inhibitory activity against L. monocytogenes by cell damage with a minimum inhibitory concentration (MIC) of 1.5 mL/L. In addition, the enzymes activity including pyruvate kinase (PK), succinic acid dehydrogenase (SDH), malic acid dehydrogenase (MDH) and respiratory chain dehydrogenase were significantly reduced, revealing that linalool can inhibit respiratory metabolism of L. monocytogenes . After treated with linalool, a significant change in metabolites was found based on multivariate statistical analysis, which involved in amino acid metabolism, central carbon metabolism, lipid metabolism, nucleic acid metabolism. Moreover, the disturbance of central carbon metabolism corresponded to the decrease in the activity of key enzymes in respiratory metabolism. These results provided a new insight into the mechanism of linalool inhibiting L. monocytogenes, and implied that linalool has the potential to prevent bacterial contamination by L. monocytogenes in the food industry. Highlights: The article was dedicated to the development of natural antibacterial agents to improve food safety. Linalool has an adverse effect on the morphological structure of L. monocytogenes. The metabolic pathway of L. monocytogenes was considered by metabolic network analysis. Omics technology and enzyme activity were used to study the inhibitory mechanism of linalool on L. monocytogenes .